Semiotics and the Modern Quebec Novel : a Greimassian analysis of Th?riault's Agaguk. - Perron, Paul J. (Toronto studies in semiotics., 1996)
Perron's Greimassian analysis of Agaguk functions as both a demonstration of the workings of that text and an example of socio-semiotic analysis, while situating literary semiotics within the larger framework of linguistic theory and literary studies.